Logistics & supply chain management - Christopher, Martin (Pearson Education, 2016)
Effective development and management of supply chain networks helps businesses cut costs and enhance customer value. This 5th edition provides the most up-to-date practical tools to manage the people and processes that allow businesses to gain and maintain competitive advantage through their supply chains.
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed April 1, 2016)
Keywords: Business logistics -- Cost effectiveness; Delivery of goods -- Management; Logistique (Organisation); Coût-efficacité; Livraison de marchandises; Gestion; Business logistics; Cost effectiveness; Delivery of goods; Management